2009
DOI: 10.1016/j.jacc.2009.04.053
|View full text |Cite
|
Sign up to set email alerts
|

The SLCO1B1*5Genetic Variant Is Associated With Statin-Induced Side Effects

Abstract: Objectives Identify SNPs associated with mild statin-induced side effects. Background Statin-induced side effects can interfere with therapy. SNPs in cytochrome P450 enzymes impair statin metabolism; the reduced function SLCO1B1*5 allele impairs statin clearance and is associated with simvastatin-induced myopathy with CK elevation. Methods The STRENGTH study was a pharmacogenetics study of statin efficacy and safety. Subjects (n=509) were randomized to atorvastatin 10mg, simvastatin 20mg, or pravastatin 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
345
5
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(377 citation statements)
references
References 26 publications
24
345
5
3
Order By: Relevance
“…Specially, Shabana et al maintained that the polymorphism showed gender-related effects on TG change following the atorvastatin treatment 31) . Although the benefits of statins in the prevention of coronary heart disease has been demonstrated by primary and secondary prevention trials [2][3][4][5][6][7][8][9][10][11][12] , there is inter-individual variability among the statin therapeutic response and some studies [32][33][34][35][36][37] recognized that genetic polymorphisms may influence the drug disposition, side effects and statin effectiveness. Due to the inconsistency in the existing literature and in order to overcome the limitation of individual studies, we performed this meta-analysis to provide a more precise and comprehensive estimation of the association between the SLCO1B1 521 T C and 388 A G polymorphisms and statin effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, Shabana et al maintained that the polymorphism showed gender-related effects on TG change following the atorvastatin treatment 31) . Although the benefits of statins in the prevention of coronary heart disease has been demonstrated by primary and secondary prevention trials [2][3][4][5][6][7][8][9][10][11][12] , there is inter-individual variability among the statin therapeutic response and some studies [32][33][34][35][36][37] recognized that genetic polymorphisms may influence the drug disposition, side effects and statin effectiveness. Due to the inconsistency in the existing literature and in order to overcome the limitation of individual studies, we performed this meta-analysis to provide a more precise and comprehensive estimation of the association between the SLCO1B1 521 T C and 388 A G polymorphisms and statin effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…35 Genes related to statin metabolism and action have been studied, including those related to liver uptake, bile excretion, and liver metabolism of statins, as well as CK activity and hereditary metabolic myopathies. 22 Although the mechanisms and genes involved are not extensively known, the following are illustrative examples: 1,22,36,37 • SLCO1B1 ---this gene encodes the organic anion transporting polypeptide 1B1 (OATP1B1), which is responsible for liver uptake of most statins. Common variants of SLCO1B1 influence the risk of muscle toxicity in patients taking simvastatin.…”
Section: Individual Factorsmentioning
confidence: 99%
“…The c388A-c521T haplotype is known as *1A (reference haplotype), c388G-c521T as *1B, c388A-c521C as *5 and c388G-c521C as *15. Carriers of *5 are at 4-to 5-fold increased risk of severe, creatine kinase-positive simvastatin-induced myopathy and 2-to 3-fold increased risk of creatine kinase-negative myopathy (46,48).…”
Section: Statinsmentioning
confidence: 99%